Faktorji osebnosti in delovna uspešnost poveljnikov - Masten, Robert (Psihološka obzorja (Ljubljana), 1995)
Some studies on personality factors and its relation to performance in the armed forces of Western countries are summarized. Often we could establish, that personality factors are not so closely connected with performance as we expect. Some problematic aspects of selection on the basis of personality factors and the relationship between personality factors and performance are discussed. We try to answer what should be done to do better prediction of performance on the basis of personality factors.
Keywords: delovna uspešnost; poveljniki; vodilni kadri; osebnostne lastnosti; vojaška psihologija; Slovenia; Slovenija